Устойчивость и колебания деформируемых систем с односторонними связями - Баженов В. А. Виктор Андреевич; Гоцуляк Е. А. Евгений Александрович; Кондаков Г. С. Геннадий Семенович; Оглобля А. И. Александр Иванович; Гуляев В. И. (Киев, Выща школа, 1989)
Исключено из фонда НТБ ТПУ